(untitled) (Brazilian Journal of Health Research, 2024)
Introduction: Sjögren’s Disease (SjD) is a multisystem autoimmune disease that can affect the lungs, leading to interstitial lung disease (ILD). Granulomatous Lymphocytic Interstitial Lung Disease (GLILD) is a rare form of ILD, commonly associated with Common Variable Immunodeficiency (CVID), but rarely described in cases of secondary immunodeficiency. Case report: We present the case of a 51-year-old female patient diagnosed with SD in 2021, who developed Nonspecific Interstitial Pneumonia (NSIP). After treatment with Cyclophosphamide and Mycophenolate Mofetil, the patient developed hypogammaglobulinemia, without fulfilling CVID criteria, suggesting secondary immunodeficiency. In 2024, decreased pulmonary function and nodular consolidations appeared in the lung bases. Pulmonary biopsy revealed lymphocytic and granulomatous infiltration, confirming GLILD. Following treatment with corticosteroids and Rituximab, the patient showed a good initial response. Discussion: Although the overlap of SjD and CVID has been described, no reports of GLILD in patients with SjD, with or without CVID, have been identified to date. Hypogammaglobulinemia in SjD is recognized as a clinical manifestation and a marker of disease activity. Pulmonary biopsy plays a key role in differentiating forms of ILD in patients with autoimmune diseases and immunodeficiencies. Conclusion: This case highlights the importance of considering GLILD as a differential diagnosis of ILD in patients with SjD and hypogammaglobulinemia, even in the absence of CVID. A multidisciplinary approach and histological investigation were essential for appropriate management and contributed to the favorable outcome of the patient.